THE EFFECTIVENESS OF YOUTUBE AS A DIGITAL LEARNING TOOL FOR IMPROVING READING COMPREHENSION AMONG ELEVENTH-GRADE STUDENTS - Ridwan Ridwan (International Journal of Community Service (IJCS), 2025)
Reading Appreciation is a abecedarian skill in English as a Foreign Language( EFL) literacy, as it enables scholars to understand written textbooks, expand vocabulary, and develop critical thinking capacities. still, numerous eleventh- grade scholars witness difficulties in reading English textbooks due to limited exposure to authentic accoutrements and the ascendance of conventional tutoring styles. This study aims to probe the effectiveness of YouTube as a digital literacy tool in perfecting scholars’ reading appreciation. Aquasi-experimental design with apre-test andpost-test control group was employed. The actors comported of 60 eleventh- grade scholars divided into an experimental group and a control group. The experimental group entered YouTube- grounded reading instruction using vids with mottoes and guided reading conditioning, while the control group was tutored through traditional text- grounded instruction. Data were collected using a reading appreciation test and anatomized through paired- sample and independent- sample t- tests. The results indicate that the experimental group achieved significantly advanced enhancement in reading appreciation than the control group( p< 0.05). These findings suggest that YouTube is an effective digital literacy tool for enhancing reading appreciation and pupil engagement, particularly in resource- limited educational surrounds.